GAMBARAN PENGGUNAAN KONTRASEPSI HORMONAL PADA KEJADIAN HIPERTENSI (Studi pada Wanita Pasangan Usia Subur di Kelurahan Tembalang) - Yuli Fatmasari; Lintang Dian Saraswati; Mateus Sakundarno Adi; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Hypertension or high blood pressure disease is a condition where a person experiences an increase in blood pressure above normal. A person is said to have hypertension if his blood pressure is always readable above 140/90 mmHg, whether with symptoms or not, the health effects caused by hypertension continue.The purpose of this study was to describe the accurrence factors of hypertension in women of fertile age couples . This research is descriptive research with cross sectional approach conducted in Tembalang. The population in this research is a woman of fertile age couples in Tembalang then taken samples as many as 100 peoples. Sampling technique with simple random sampling. Measurements of blood pressure and filling questionnaire. From 100 respondents of the study found 47% of respondents who are hypertention. The highest proportion of hypertension on the respondents who have duration of hormonal contraceptive use >5 years (62.8%), types of contrasepsi hormonal used types of pil (62.5%), knowledge of good hormonal contraceptive side effects (48.1%). Required checks of blood presure on a regular basis, maintaining a healthy lifestyle and more wise in using hormonal contraception.